Interchange A Quarterly Review of Education - Winchester, Ian.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Interchange, an externally refereed educational quarterly, embraces educational theory, research, analysis, history, philosophy, policy and practices. The journal seeks to foster exchanges among practitioners, policy-makers, and scholars and to provide a forum for comment on issues and trends in education. The journal specializes in frank argumentative articles on the fundamental purposes of education. Its articles typically challenge conventional assumptions about education and higher education and do so from perspectives in philosophy or the social sciences. A special feature is the publishing of responses, and frequently response to responses, in the same issue as the article which provoked them. Its authors are scattered throught the world. All contributions to this journal are peer reviewed.
Keywords: Educational policy; ducation and state; Education -- Philosophy; Educational Policy and Politics; Educational Philosophy